PEMUKIMAN HYVE: KEHIDUPAN KOLEKTIF UNTUK MILENIAL - Rainier Lazar Hadiprodjo; Martin Halim (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The millennial generation has a very wide and large opportunity and opportunity to innovate in this era. Therefore, this millennial generation is a great asset to realize national independence in all aspects. Currently the number is around 30% of the total population of Indonesia and is expected to continue to grow. It is predicted that the millennial generation will find it difficult to own a home in the next few years. Coupled with a pandemic that limits the movement of people. Therefore it is necessary to carry out in-depth research on the space requirements that are very much needed for millennials, so that they can create new parameters for housing specifically for millennials who have flexible and practical preferences. "The Hyve Settlement" project aims to provide efficient and affordable housing for Millennials. By presenting residential module units, and equipped with flexible and compact furniture so as to increase the space efficiency of the residence. As well as presenting communal living space to increase space efficiency and also create social development for other residents. Presenting supporting programs like public facilities to improve the quality of life for residents. Keywords:  Collective, Dwelling, Efficieny, Flexibelity, Millenial Abstrak Generasi milenial memiliki peluang dan kesempatan berinovasi yang sangat luas dan besar di era ini. Oleh karena itu, generasi milenial ini adalah modal besar untuk mewujudkan kemandirian bangsa dalam segala aspek. Saat ini jumlahnya sekitar 30% dari total penduduk Indonesia dan diperkirakan akan terus bertambah. Diprediksi generasi milenial akan sulit memiliki rumah dalam beberapa tahun ke depan. Ditambah lagi dengan terjadinya pandemi yang membatasi pergerakan masyarakat. Oleh karena itu diperlukan dilakukan penelitian mendalam terhadap kebutuhan ruang yang sangat dibutuhkan bagi para kaum milenial, sehingga dapat menciptakan parameter baru pada hunian yang dikhususkan bagi kaum milenial yang memiliki preferensi serba fleksibel dan praktis. Project “The Hyve Settlement” bertujuan untuk menghadirkan hunian yang efisien serta terjangkau bagi kaum Milenial. Dengan menghadirkan hunian modul unit, serta dilengkapi dengan furniture yang fleksibel dan compact sehingga meningkatkan space efficiency pada hunian. Serta menghadirkan communal living space untuk meningkatkan efisiensi ruang dan juga menciptakan social development terhadap penghuni lainnya. Menghadirkan program penunjang layaknya fasilitas umum untuk meningkatkan kualitas hidup para penghuni.